2015
DOI: 10.1148/radiol.2015142566
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Digital Breast Tomosynthesis for Depicting Breast Cancer Subgroups in a UK Retrospective Reading Study (TOMMY Trial)

Abstract: The addition of DBT increased the sensitivity of 2D mammography in patients with dense breasts and the specificity of 2D mammography for all subgroups. The use of synthetic 2D DBT demonstrated performance similar to that of standard 2D mammography with DBT. DBT is of potential benefit to screening programs, particularly in younger women with dense breasts. (©) RSNA, 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 30 publications
(36 reference statements)
3
117
1
3
Order By: Relevance
“…This study showed a high sensitivity and specificity of DBT over DM. This advantage of DBT over DM provides two main benefits, namely increased rates of cancer detection and reduced callback rates [15-18, 23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed a high sensitivity and specificity of DBT over DM. This advantage of DBT over DM provides two main benefits, namely increased rates of cancer detection and reduced callback rates [15-18, 23]. …”
Section: Discussionmentioning
confidence: 99%
“…By combining information from different projections, DBT improves the differentiation of the adjacent anatomical structures, alleviating the superimposition effect [13]. More recent studies indicate about 30% increased DBT sensitivity and specificity compared with DM [14], with a 40% reduction in callback in screening [15-18]. DBT has been implemented in Kuwait during the last 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a few reader studies and limited prospective studies that compared the performance of s2D mammography versus digital mammography/DBT in a clinical setting (11)(12)(13)(14)(15). Results were mixed: two prospective studies and one reader study showed similar performance between both combination modalities (11,(13)(14)(15), whereas another reader study showed lower sensitivity and comparable specificity in s2D mammography and DBT (referred to as s2D/DBT) versus digital mammography/DBT. In one prospective study, symptomatic patients were included in the s2D mammography and digital mammography/DBT screening group so this cohort was not a true screening population (11).…”
Section: Patient Datamentioning
confidence: 99%
“…BREAST IMAGING: Implementation of Synthesized Two-dimensional Mammography Zuckerman et al interpretation, which may have led to a selection bias (14,15). The purpose of our study was to evaluate the early implementation of s2D mammography in a population screened entirely with s2D/DBT and compare recall rates and cancer detection rates to historic outcomes of digital mammography/DBT screening.…”
mentioning
confidence: 99%
“…The results indicated 55, 48 and 30% improvement in true positive detection when a 2D-3D setup was used in lieu of traditional setup in Houston, STORM, and Oslo studies, severally [48]. In TOMMY trial in UK, 2015, increased specificity (by 9%) for all studied groups and elevated sensitivity (by 7%) for dense breasts was observed as a result of using digital and film screening [49]. A 2016 review also reported fewer recall rates using the DBT [50].…”
Section: Digital Breast Tomosynthesis (Dbt)mentioning
confidence: 95%